Surgery and Radiosurgery for Acromegaly: A Review of Indications, Operative Techniques, Outcomes, and Complications - Marquez, Yvette (Hindawi Publishing Corporation, 2012)
Among multimodality treatments for acromegaly, the goals of surgical intervention are to balance maximal tumor resection while preserving normal pituitary function and maintaining patient safety. The resection of growth hormone-(GH-) secreting pituitary adenomas in the hands of experienced surgeons results in hormonal remission in 50–70% of patients. Acromegalic patients often have medical comorbidities and anatomical variations complicating anesthesia and surgical management. Despite these challenges, complications such as CSF leak or new hypopituitarism following surgery remain uncommon. Over the past decade, endoscopic approaches to pituitary tumors have improved visualization and facilitated identification of additional tumor using angled telescopes. Patients with persistent acromegaly following surgery require continued medical and/or radiation-based interventions. The adjunctive use of stereotactic radiosurgery offers hormonal remission in 40–50% of patients. In this article, the current preoperative evaluation, indications for surgery, surgical approaches, role of radiosurgery, complications, and remission criteria following operative resection of GH adenomas are reviewed.